Efectos de la fermentación láctica del lactosuero y alcohólica del mucílago de cacao en la concentración final de una bebida alcohólica - Espinoza Vaca, Héctor Aníbal (2018)
In this research work sweet whey was taken advantage, from the criollo cheese produced by cocoa mucilage of the CCN 51 variety, as a must combined between these two raw materials to obtain an alcoholic beverage. For the solids present in the sweet whey it was necessary to apply a filtration by gravity, in a cold environment using filter paper in order to reduce the initial% of fat present in this raw material, minimize the enzymatic reactions and acidification produced by the lipids . For the fermentation to be expressly alcoholic, the whey was hydrolyzed with an enzyme (lactase) Ha-5200. Preliminary tests were carried out where the results showed that a correction of the musts with sodium bicarbonate in relation to 0.3% was necessary. Three treatments were established where the mucilagous matter from cocoa CCN51 was in greater ratio for the three treatments under study, where they were established as follows, T1 (10% sweet whey - 90% cocoa mucilage); T2 (20% sweet whey - 80% cocoa mucilage); T3 (30% sweet whey - 70% cocoa mucilage). By controlling physicochemical properties such as: Temperature, pH, titratable acidity and ° Brix it was established that the fermentation time for the musts was 60 hours. A DCA design of three treatments with five replicates were used. The results obtained determined T1 as the best treatment corroborated with bibliographic reports, also framed as the best treatment in sensory evaluation as the most preferred.